Effectiveness of a Serious Game Design and Game Mechanic Factors for Attention and Executive Function Improvement in the Elderly: A Pretest-Posttest Study - Ying-Kit Wong; Chih-Fu Wu; Yung-Hsiang Tu (Applied Sciences, 2022)
Attention allows us to focus and process information from our environment, and executive function enables us to plan, work, and manage our daily lives. As individuals become older, both of these cognitive abilities decline. It is essential for the elderly to perform more cognitive exercises. Previous studies have shown that arithmetic calculations require attention span and that playing video games requires executive function. Therefore, we developed a serious game involving mental arithmetic calculations specifically for improving attention span and executive functions. Our objective was to analyze the effectiveness of the game and the efficacy of the game’s mechanic factors affecting attention span and executive function in the elderly. Forty elderly volunteers who are over 60 years of age were invited to join an eight-week cognitive training program through an elderly social welfare center. Four assessment tests were used in pre-test and post-test before and after the training period. D-CAT and SAT are used for screening attention span; TMT-A and TMT-B are used for screening executive function. They were instructed to play the game for at least 15 min per day, 5 days per week, for a total of 8 weeks. There were three independent variables (difficulty, pressure, and competition) with two parameters that could be selected. A paired-sample t-test showed the effective results by comparing the pre-test scores and post-test scores of the cognitive training. There were significant improvements in attention span and executive functions. The mixed repeated-measure ANOVA and MANCOVA results showed that two game mechanic factors (difficulty and pressure) had a significant effect and an interaction effect, but the other factor (competition) had a non-significant effect. In conclusion, the game showed a significant enhancement in both attention span and executive functions after training, and the difficulty factor and the pressure factor were shown to have an effect, but the competition factor was shown to have no effect.